Nutritional label knowledge & cardiovascular disease determinants among mothers in Malang City - Erliana, Ummu Ditya; Kurniasari, Fuadiyah Nila; Harti, Leny Budhi (Caring: Jurnal Pengabdian Masyarakat, 2024)
Nutrition labels serve as a guide for consumers to select healthier food options, potentially preventing obesity and cardiovascular diseases. However, many mothers lack sufficient knowledge regarding nutritional information on food labels. The goal of this community service activity is to enhance mothers' understanding of food and beverage nutrition labels, enabling them to make healthier choices for their families. The activities include nutrition education, counseling, and nutrition screenings for the mothers. The effectiveness of the educational intervention is assessed using a pre-post test questionnaire. The differences of the pre-post test were analyzed using the Wilcoxon Signed-Rank Test. The result of this activity showed that post-test scores were higher than pre-test scores about 92.94 and 72.63 respectively (p=0.0035). In conclusion, there was a notable improvement in knowledge regarding nutritional labels following the educational outreach, indicating that such interventions can effectively enhance understanding and promote healthier dietary choices among mothers